More Talk, More Support? The Effects of Social Network Interaction and Social Network Evaluation on Social Support via Social Media - Han R (Psychology Research and Behavior Management, 2023)
Ruixia Han1,2 1School of Media and Communication, Shanghai Jiao Tong University, Shanghai, 200240, People’s Republic of China; 2Institute of Cultural Innovation and Youth Development, Shanghai Jiao Tong University, Shanghai, 200240, People’s Republic of ChinaCorrespondence: Ruixia Han, School of Media and Communication, Shanghai Jiao Tong University, Shanghai, 200240, People’s Republic of China, Tel +86-21-34202854, Fax +86-21-34202854, Email annahan08@sjtu.edu.cnIntroduction: Do more friends and more frequent interactions on social media result in more social support? The impact of variables such as interaction size and frequency on the social support individuals receive via social platforms has been studied from the perspective of social networks, and some studies have focused on the role of interaction topics from the perspective of private engagement. Little research has been done on the impact of affect control embedded in social networks. The emotion-first nature of social media and the rise of affect control theory mean that this perspective deserves attention.Methods: This study examined 634 WeChat users by means of an online survey on variables related to social media use, such as social network size, interaction frequency, users’ evaluation of network members, and personal topic involvement, and then tested the influencing mode of these variables on people’s perceived social support through chain mediation analysis using Model 80 of the process in spss.Results: (1) Interaction size influences perceived social support by affecting personal topic involvement; (2) Interaction frequency does not directly mediate the relationship between interaction size and perceived social support, but mediates the relationship in a chain by affecting personal topic involvement; and (3) Social network evaluation not only directly mediates the relationship between interaction size and perceived social support, but also further mediates the relationship by influencing personal topic involvement.Conclusion: The study confirmed the role of affective control in people’s perceived social support through social network interactions. Those people talk about personal matters with individuals who have greater evaluation, potency, and activity in social networks are more likely to get perceived social support. The study draws our attention to the role of affection control in interpersonal relationships in the era of social media mediating people’s daily interactions.Keywords: social media, social interaction, social support, interaction frequency, EPA